2017
DOI: 10.1080/19396368.2017.1378936
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in patients with recurrent pregnancy loss is associated with lymphocyte population aberration

Abstract: This study was designed to investigate the relationship of insulin resistance (IR) and cellular immune abnormalities associated with women with recurrent pregnancy loss (RPL). Women with RPL were divided into two groups according to their homeostasis model assessment for IR (HOMA-IR) scores. The IR group received metformin approximately 3 months before pregnancy. The percentage of lymphocyte subsets and other blood biochemical indices were tested. The HOMA-IR and fasting serum insulin levels were related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…It has been demonstrated in mice that lymphocytes participate in the pathogenesis of IR (49). Yan et al found that a far greater proportion of newly diagnosed RPL patients with IR had an aberrant CD3 + CD4 + , and CD56 + CD16 + cell population compared to RPL patients without IR (34). Our study found that an increase in TG levels positively associated with an increased CD3 + CD4 + /CD3 + CD8 + ratio.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It has been demonstrated in mice that lymphocytes participate in the pathogenesis of IR (49). Yan et al found that a far greater proportion of newly diagnosed RPL patients with IR had an aberrant CD3 + CD4 + , and CD56 + CD16 + cell population compared to RPL patients without IR (34). Our study found that an increase in TG levels positively associated with an increased CD3 + CD4 + /CD3 + CD8 + ratio.…”
Section: Discussionsupporting
confidence: 59%
“…An increased ratio of CD4 + /CD8 + lymphocytes was found in lipopolysaccharide (LPS) challenged pigs (32). IR was reported to be related to the abnormal percentage of lymphocyte subsets in RPL (33,34). A recent study revealed that a decrease of regulatory B cells (CD19 + CD24 hi CD38 hi ) in peripheral blood is associated with IR, and can increase the risk of postprandial hyperinsulinemia (35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation